TAXONOMY AND FAUNAL AFFINITY OF LATE CARNIAN RHAETIAN CONODONTS IN THE SOUTHERN CHICHIBU BELT, SHIKOKU, SW JAPAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Conodonts from the latest Carnian - Middle Norian pelagic limestone and Late Norian - Rhaetian bedded chert-section at Hisaidani, southern Chichibu Belt, Shikoku, SW Japan, are described. Taxonomy of conodont-genera Metapolygnathus Hayashi, Ancyrogondolella Budurov, MockinaKozur and Misikella Kozur & Mock is discussed. Middle Norian Mockina sakurae n. sp., M. shamiseni n. sp. and Late Norian M. hisaidaniensisn. sp. are described.The affinities of the Hisaidani - fauna are rather Tethyan. The Early - Middle Norian conodont-association at Hisaidani is dominated by Ancyrogondolella spatulata (Hayashi). Towards the Middle and Late Norian, affinities with Pacific taxa are present. The three new species provide also a provincial character that typifies the pre-accretionary Izanami plateau from which the rocks of Hisaidani were derived.